Glochidion montanum Thw. (Euphorbiaceae) a Tree New to the Flora of India - Bahadur, K. N.; Gaur, R. C.; Sahni, K.C. (Indian Forester, 1973)
The paper records the occurrence of Gloehidion montanum Thw., a tree of the family Euphorbiaceae, in India. It was collected from forests of Goa in the Western Ghats. So far, the species was considered endemic to Sri Lanka. Brief notes on nomenclature, description, infraspecific and interspecific differences, phytogeography, a key for identification and an illustration are provided.